ANALISIS KECERDASAN INTERPERSONAL PESERTA DIDIK PADA PEMBELAJARAN EKONOMI DI KELAS X SMA NEGERI 2 TANJUNG RAJA - Wulandari; Riswan Jaenudin; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2016)
This research aims to describe the interpersonal intellegence at economic learning of tenth grade students in SMA Negeri 2 Tanjung Raja at second semester in 2014/2015. The method of this research was descriptive. The population were all students of tenth grade at SMA Negeri 2 Tanjung Raja that amounted 145 students. The sampel of his research was using proportional random sampling, so that get 100 students. The data collection using questionnaire, interviews, and observation. The data were analyzed by quantitative and qualitative method. The result of this research show that, overall the interpersonal intellegence of students was on high category, it means that students could make the social relation on economics learning well. Seen from social sensitivity on high category (80,10%) consist of emphaty very high (84,52%) dan prosocial high (75,67%); social communication on high category (80,32%) consist of indicator can doing communication with decent high (74,65%) and listenig efectively very high (85,99%); social insight on high category (80,43%) consist of indicator self awareness very high (83,85%) and insight of ethics and social situasion high (77,02%). suggested for teachers to improve the guidance and counseling so that some interpersonal intellegence problem which found in this research can be repair so that learning procces especially economic learning can performing well.